Characterization of Novel Lytic Myoviridae Phage Infecting Multidrug-Resistant Acinetobacter baumannii and Synergistic Antimicrobial Efficacy between Phage and Sacha Inchi Oil - Phitchayapak Wintachai; Supayang Piyawan Voravuthikunchai (MDPI AG, 2022)
Multidrug-resistant (MDR) strains of Acinetobacter baumannii have become a major cause of hospital-acquired infections, resulting in an increase in morbidity and mortality worldwide. Many alternative treatments, including phage therapy, are attractive approaches for overcoming problems posed by antibiotic resistance. A newly isolated phage, vWUPSU-specific MDR A. baumannii, showed a narrow host range against MDR A. baumannii. This research was conducted to isolate, characterize, and apply the phage with sacha inchi oil as an alternative antimicrobial agent. Genome analysis suggested that phage vWUPSU is a novel phage belonging to the family Myoviridae, order Caudoviridae. This phage prevented biofilm formation and eradicated preformed biofilms in a dose-dependent manner. In addition, a synergistic antimicrobial effect of the interaction between phage vWUPSU and sacha inchi oil on planktonic cells was observed. The combination of phage and sacha inchi oil significantly inhibited and removed biofilms, compared with the effects of either single treatment. The results of this work indicate that phage vWUPSU could potentially be applied to control MDR A. baumannii. The antibacterial and antibiofilm activities of the combination of phage vWUPSU and sacha inchi oil have attracted significant interests in the development of antibacterial phage products as beneficial treatment options.